The Effect of Influencer Marketing and Online Customer Reviews on Purchase Decisions of Local Running Shoes: The Mediating Role of Perceived Value and Perceived Trust - Rudy Faishol; Anna Widiastuti; Mohammad Rifqy Roosdhani (Jurnal Mirai Management, 2026)
The rapid advancement of digital technology has fundamentally transformed the way consumers interact with markets and brands. This transformation indicates a significant shift in consumer consumption behavior toward digital environments, where purchase decisions are increasingly influenced by online information, user-generated reviews, and digital promotional content. This study aims to examine the effects of influencer marketing and online customer reviews on purchase decisions, with perceived value and perceived trust serving as mediating variables. The research employs an explanatory quantitative approach involving 190 respondents from the young adult demographic aged 20–40 years in Jepara Regency, who have purchased, used, and/or owned local running shoes. Respondents were selected using purposive sampling, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that influencer marketing and online customer reviews do not have a significant direct influence on purchasing decisions. The influence of influencer marketing on purchasing decisions operates through the formation of perceived trust. Meanwhile, the influence of online customer reviews on purchasing decisions operates through the formation of perceived value and perceived trust. These findings strengthen consumer behavior theory and perceived value theory by positing perceived value and perceived trust as important mediating mechanisms that transform marketing stimuli into actual purchase decisions by local running shoe consumers.